(untitled) (Palíndromo, 2020)
This article deals with the research “Desenho de nuvem” developed in the Institutional Program of Scientific Initiation of the Universidade Federal do Espírito Santo (under the guidance of Prof. Dr. Diego Rayck) and as a Bachelor of Arts Course Completion (under the guidance of Prof Dr. Aline Dias). The research is an artistic process investigation into the “Diário de nuvem” series, work in progress since May 2017, which includes the daily realization of a cloud observation drawing. By investing in the continuity of this artistic proposal simultaneously with the theoretical investigation about notions of drawing, landscape and daily recording practices found in conceptual art, inserting itself in the methodological framework of art research. Given the issues raised by “Diário de nuvem” artists On Kawara and Francis Alÿs are taken as reference. In the reflections on the notions of place and landscape are taken the concept of topophilia of Yi-Fu Tuan (2012) and the theory of space immersion by Emanuele Coccia (2018).